Neural deletion of Sh2b1 results in brain growth retardation and reactive aggression. Issue 4 (5th January 2018) - Jiang, Lin; Su, Haoran; Keogh, Julia M.; Chen, Zheng; Henning, Elana; Wilkinson, Paul; Goodyer, Ian; Farooqi, I. Sadaf; Rui, Liangyou
Abstract : Psychiatric disorders are associated with aberrant brain development and/or aggressive behavior and are influenced by genetic factors; however, genes that affect brain aggression circuits remain elusive. Here, we show that neuronal Src‐homology‐2 (SH2)B adaptor protein‐1 ( Sh2b1 ) is indispensable for both brain growth and protection against aggression. Global and brain‐specific deletion of Sh2b1 decreased brain weight and increased aggressive behavior. Global and brain‐specific Sh2b1 knockout (KO) mice exhibited fatal, intermale aggression. In a resident‐intruder paradigm, latency to attack was markedly reduced, whereas the number and the duration of attacks was significantly increased in global and brain‐specific Sh2b1 KO mice compared with wild‐type littermates. Consistently, core aggression circuits were activated to a higher level in global and brain‐specific Sh2b1 KO males, based on c‐fos immunoreactivity in the amygdala and periaqueductal gray. Brain‐specific restoration of Sh2b1 normalized brain size and reversed pathologic aggression and aberrant activation of core aggression circuits in Sh2b1 KO males. SH2B1 mutations in humans were linked to aberrant brain development and behavior. At the molecular level, Sh2b1 enhanced neurotrophin‐stimulated neuronal differentiation and protected against oxidative stress–induced neuronal death. Our data suggest that neuronal Sh2b1 promotes brain development and the integrity of core aggression circuits, likely through enhancing neurotrophin signaling.— Jiang, L., Su, H., Keogh, J. M., Chen, Z., Henning, E., Wilkinson, P., Goodyer, I., Farooqi, I. S., Rui, L. Neural deletion of Sh2b1 results in brain growth retardation and reactive aggression. FASEB J. 32, 1830–1840 (2018). www.fasebj.org